Interdisciplinary bachelor's degree in health: analysis of a new higher education curriculum in Brazil - Layza Castelo Branco Mendes; Andrea Caprara (Faculdade de Medicina de Botucatu (Unesp), 2012)
Brazilian public universities are undergoing an intense process of change in search of solutions to transform themselves into institutions that are more attuned to 21st century social needs. In this regard, the aim of this study was to analyze a new higher education curriculum offered at the Federal University of Bahia (UFBA): the Interdisciplinary Bachelor's degree in Healthcare. This was a preliminary qualitative investigation, accomplished as a case study. The methodological tools used include document analysis, open interviews and participant observation. It was seen that the teachers were engaged in the process of putting together a course that promotes training of professionals qualified to undertake social development. It was also noted that the students were themselves proving to be capable of deep critical reflection on social issues. It was therefore concluded that the case studied has provided the results expected by the higher education institution hosting the course.